Effect of the COVID-19 national lockdown on road traffic accident fatalities involving traumatic brain injury: A retrospective review of Salt River Mortuary cases - Mokgotho, Mahlatse (Department of Pathology, 2025)
Background: Low- and middle-income countries have reported higher traumatic brain injury (TBI) incidence and mortality rates in cases involving road traffic collisions (RTCs). In South Africa, RTCs are commonly reported as contributors to death; however, the current burden of TBI attributable to these deaths is unknown. Additionally, movement restrictions and behavioural changes introduced during the COVID-19 nationwide lockdown have been shown to affect injury patterns in general, but their impact on TBI is undocumented. This study aimed to investigate the epidemiology and patterns of TBI-associated deaths attributable to RTCs before and during the nationwide lockdown in South Africa. Methods: Autopsy reports of TBI-associated deaths due to RTCs, reported to Salt River Mortuary between 1 January 2019 and 31 December 2020, were reviewed. Results: A total of 616 RTCs, from the 7694 total caseload, were included with RTC-related TBIs accounting for 6.51% of the caseload across two years. Males were three times more likely to present with RTC-related TBIs compared to females. Individuals aged 30-39 years were at the highest risk of RTCs, and the median age of those with TBI (34 years) was significantly younger than those without (39 years, p < 0.001). Furthermore, the proportions of the TBI cases were comparable across all road user groups, all were equally likely to sustain TBI in an RTC. Two-thirds (66.18%) of individuals died before hospital admission. Of the 47.16% deceased individuals whose alcohol concentration was detectable, 92.96% had an alcohol level of ≥ 0.05 g/100 mL however we found no significant association between alcohol consumption and sustaining a TBI. Conclusion: These findings indicated that younger individuals are at a higher risk of TBI in RTC-related deaths. Furthermore, injury patterns did not seem to differ between the periods before compared to during the COVID-19 lockdown.